Ein schmackhafter Beifang - Pandalus - Kühlmorgen-Hille, G. (1982)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010